Bio-inspired multistable metamaterials with reusable large deformation and ultra-high mechanical performance. (October 2019) - Zhu, Shaowei; Tan, Xiaojun; Wang, Bing; Chen, Shuai; Hu, Jiqiang; Ma, Li; Wu, Linzhi
Abstract: Multistable mechanical metamaterials are known for their unique mechanical characteristics, such as snap-through behaviors, negative stiffness effects, and reusability, thus they exhibit unique advantages in some applications. However, traditional multistable materials exhibit fairly low strength and stiffness. Herein, inspired by some activities and mechanisms in the biological organs, a new type of multistable metamaterial comprising a periodic arrangement of sleeves is designed and investigated. The compression experiments show that the material is characterized by typical multistable behaviors and exhibits other advantages such as lightweight, ultra-high stiffness and strength. Moreover, the cycle experiment shows that the material is reusable even though very large deformation occurs. The mechanism of those behaviors is analyzed, and a theory is established for the design of such materials. Based on this outcome, the effects of the important parameters that can control the materials to exhibit snap-through behavior or friction-dominated behavior are discussed. Graphical abstract: